2005
DOI: 10.1081/ja-200052290
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Ecstasy Users in São Paulo, Brazil

Abstract: The present study was aimed at identifying patterns of Ecstasy (methylenedioxymethamphetamine-MDMA) use in the city of São Paulo. Ecstasy users were recruited through the snowball technique. Using the same technique, a non-user control group was recruited among individuals that had never tried the drug but shared with users a similar life style. Users (N = 52) and non-users (N = 52) were interviewed in order to obtain data on socio-demographic characteristics and use of psychoactive drugs. In addition, levels … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
20
0
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 20 publications
2
20
0
6
Order By: Relevance
“…These results confirmed our hypothesis that the consumption of ecstasy is more frequent in districts with high socioeconomic levels and are in line with others studies that had also found that ecstasy users come from upper classes (Almeida, Silva, 2003;Almeida, Silva, 2005;Battisti et al, 2006;Almeida, Bizeto, Silva, 2007;Almeida, Garcia-Mijares, Silva, 2009).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…These results confirmed our hypothesis that the consumption of ecstasy is more frequent in districts with high socioeconomic levels and are in line with others studies that had also found that ecstasy users come from upper classes (Almeida, Silva, 2003;Almeida, Silva, 2005;Battisti et al, 2006;Almeida, Bizeto, Silva, 2007;Almeida, Garcia-Mijares, Silva, 2009).…”
Section: Discussionsupporting
confidence: 82%
“…Another study, in the city of São Paulo, enrolling 52 ecstasy users of both genders showed that the drug was usually consumed in the company of several people (63%) in contexts related to night leisure, such as rave parties (78.8%), dancing clubs (69.2%) and parties (53.8%) (Almeida, Silva, 2003). In addition, a significant difference comparing ecstasy users with nonusers in relation to the frequency of rave attendance was reported: 65.3% of users go to raves more than once a month in contrast to only 16.7% of non-users (Almeida, Silva, 2005). A concerning fact from a recent study drew the attention to the possibility that participants were dependent on club drugs and found that severe dependence was more likely among those who reported recent use of ecstasy (Ding et al, 2013).…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Éste es un patrón similar al encontrado en otros países. [30][31][32] Algunos investigadores han señalado que el uso de drogas puede estar involucrado como marcador del mal control de la diabetes, en particular en la población de adolescentes, quienes a menudo ignoran las complicaciones de su uso aumentando el riesgo de muerte súbita entre los mismos. 33 Este peligro debería ser enfatizado en todas las intervenciones médicas con adolescentes.…”
unclassified
“…Corrobora esse resultado pesquisa que indica alteração no sistema 5-HT em usuários abstinentes há 12 meses, ainda que não possa ser descartada a hipótese de mudanças serotonérgicas em função de condições pré-mórbidas (Gerra et al, 2000). Ou seja, há indícios da associação entre uso de ecstasy e depressão, ainda que para alguns pesquisadores esta relação não seja clara (de Almeida & Silva, 2005;Sumnall & Cole, 2005).…”
Section: Conseqüências Psiquiátricas Segundo Documento Publicado Pelunclassified